¿Qué estilos de liderazgo se relacionan con la motivación y el desempeño laboral de los colaboradores de la organización Unisys Technical Services [UTS] de Rionegro? - Rojas Estrada, Carolina (Psicología, 2017)
Abstract This research wants to gain a bigger understanding of the existing dynamic among leadership, motivation and performance, as well as to establish the type of leadership that are related to motivation and performance and the influence that leadership has on motivation and performance. This study has qualitative research approach; It used a sample of 60 people, and It was supported by the focus group technique to collect data and the content analysis technique to codify the information. As results, it was found that charismatic, transactional and transformational leadership types were more found at UTS Rionegro, as well It was concluded that these types of leadership motivate and influence the performance of UTS Rionegro´s employees and aspects such as emotional intelligence and stress management are very important elements for leadership.